2011
DOI: 10.1002/jhet.626
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl 1,4‐dihydro‐4‐oxo‐3‐quinolinecarboxylates by a tandem addition‐elimination‐SNAr reaction

Abstract: The ethyl 1,4‐dihydro‐4‐oxo‐3‐quinolinecarboxylate ring structure, important in several drug compounds, has been prepared in two steps from ethyl 2‐(2‐fluorobenzoyl)acetate. Treatment of this β‐ketoester with N,N‐dimethylformamide dimethyl acetal gives a 97% yield of the 2‐dimethylaminomethylene derivative. Reaction of this β‐enaminone with primary amines in N,N‐dimethylformamide at 140°C for 48 h then affords the 1,4‐dihydro‐4‐oxo‐3‐quinolinecarboxylate esters in 60–74% yields by a tandem addition‐elimination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…In fact, the target heterocycles were produced in similar yields from all amines when the R group was primary, secondary or aromatic. Our previous work indicated that primary amines incorporating a tertiary R group reacted poorly, and this was borne out in this study where tert ‐butylamine (entry g ) gave the lowest yield. Nevertheless, hindered aromatic amines, such as 2‐methylaniline ( o ‐toluidine, entry o ), afforded dihydronaphthyridine 7o in a respectable 78% yield, despite the steric congestion created by the ortho methyl group.…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations
“…In fact, the target heterocycles were produced in similar yields from all amines when the R group was primary, secondary or aromatic. Our previous work indicated that primary amines incorporating a tertiary R group reacted poorly, and this was borne out in this study where tert ‐butylamine (entry g ) gave the lowest yield. Nevertheless, hindered aromatic amines, such as 2‐methylaniline ( o ‐toluidine, entry o ), afforded dihydronaphthyridine 7o in a respectable 78% yield, despite the steric congestion created by the ortho methyl group.…”
Section: Resultsmentioning
confidence: 60%
“…, entries d and f ) gave the carboxylic acids rather than the ester products. This anomaly was not encountered in our previous work to prepare 1,4‐dihydro‐4‐oxo‐3‐quinolinecarboxylate esters , or from any other amine in this study. Attempts to suppress this process by running the reaction at lower temperature (90–100°C) were unsuccessful and gave ester‐acid mixtures.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…To a stirred suspension of 18 (200 g, 0.75 mol) in toluene (2.3 L) was added DMF-DMA (401 mL, 3.02 mol). The mixture was stirred at 90-100 C for 24 h and then cooled to » 10 C. The resulting yellow solid was collected, washed with cooled toluene (115 mL £ 3), and dried under reduced pressure to give 19 (214 g, 89%) as a bright-yellow powder, which was used directly at the next step, mp: 174-175 C. 1 N-(7-Ethoxy-4-oxo-1,4-dihydroquinolin-6-yl)acetamide (20). Compound 19 (180 g, 0.56 mol) and Raney-Ni (wet, 20 g) were added to DME (4.6 L), and stirred for 12 h at rt under 1 atm of hydrogen.…”
Section: Methodsmentioning
confidence: 99%